Titans. The complete third season [videorecording (DVD)]. - Thwaites, Brenton, 1989-; Diop, Anna, 1988-; Croft, Teagan, 2004-; Potter, Ryan, 1995- (Warner Bros., 2022)
In the explosive third season, Jason Todd's journey as Robin comes to a gruesome end only for him to return to Gotham as Red Hood with a vengeance to take down his old team. Meanwhile, Barbara Gordon, the former Batgirl and current acting Commissioner of the Gotham City Police Department is wary of the Titans now being back in Gotham, but her history with Dick Grayson leads her to accept their help in the GCPD's investigation of Red Hood. Also assisting the investigation is Dr. Jonathan Crane, a one-time supervillain and current inmate at Arkham Asylum.